Analysis of E-Leadership Practices in Ameliorating Learning Environment of Higher Education Institutions: Wajeeha Aurangzeb،Uzma Mazhar (PJDOL, 2023)
Information and communication technologies have made a profound and deep impact on educational organizations, especially at higher level. Leaders are required to adopt ICT tools not only for their own competence but for meeting the demands of e-leadership and changing teaching-learning ecology. Current study aimed at examining and elucidating the practices involved in adoption and enrichment of e-leadership processes at higher education level through qualitative research approach. Research respondents included 50 employees in higher education level working under the domain of leadership. Semistructured interviews helped to extract major themes and sub-themes under the framework of replacement, amplification and transformation of e-leadership practices. Findings revealed that e-leadership practices arecurrently at the replacement phase of ICT integration.